The 8th International Conference on Time Series and Forecasting - Rojas, Ignacio; Pomares, Hector; Valenzuela, Olga; Rojas, Fernando; Herrera, Luis; Kaufman, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of ITISE 2022 is to create a friendly environment that could lead to the establishment or strengthening of scientific collaborations and exchanges among attendees. Therefore, ITISE 2022 is soliciting high-quality original research papers (including significant works-in-progress) on any aspect time series analysis and forecasting, in order to motivating the generation and use of new knowledge, computational techniques and methods on forecasting in a wide range of fields.